THE EFFECT OF INTENSIVE GLYCEMIC CONTROL ON THE FACTORS DETERMINING PREDICTION COMPLICATIONS OF ACUTE MYOCARDIAL INFARCTION IN PATIENTS WITH TYPE 2 DIABETES - A. I. Fedotova; I. N. Vorozhtsova; I. V. Маksimov; T. Yu. Rebrova; S. A. Аfanasiev; A. M. Gusakova; T. E. Suslova; V. A. Маrkov (Бюллетень сибирской медицины, 2015)
Objective. To determine predictors of complications of myocardial infarction (MI) in patients with type 2 diabetes (2TDM) and it’s value of intensive glycemic control during insulin infusion.Methods. The study included 112 patients with MI and 2TDM at first day of hospital admission with blood glucose level above 7.8 mmol/l. Prognosis of combined study endpoint included the death and ma-jor complications of MI for the hospital and long-term (6-month) stages. The statistical analysis was per-formed (Statistica 6.0 for Windows). The predictive value was assessed with ROC-curves analysis meth-od.Results. Intensive glycemic control with insulin infusion reduced the activity of lipid peroxidation and improve prediction of study endpoint. Predictors of adverse hospital prognosis of MI in association with type 2 diabetes were hyperglycemia on admission above 10 mmol/l, and increase of C-peptide. The in-crease of C-peptide in the 1st and 7th day, hs-CRP on day 1, diene conjugates on the 7th day and glucose level on admission above 8.9 mmol/l (patients without 2TDM) and 14.3 mmol/l (patients with 2TDM) had the 6-month predictive value.Conclusion. The strict achievement of the target level of glucose in acute MI improves it’s prognosis at the hospital and at a 6-month prospective study.